Pengaruh Kualitas Sistem Informasi Keuangan Daerah terhadap Kepuasan Aparatur Pemerintah Daerah Menggunakan Model Delone dan Mclean - Arifin, Jabal Firdaus; Pratolo, Suryo (Journal of Accounting and Investment, 2012)
This study aims to determine the effect of regional financial information system to local government officer. This study obtained a result that: the quality SIKD had positive effect on satisfaction of the local government officer, the quality of information from SIKD had no positive effect on satisfaction of the local government officer, and quality SIKD had no positive effect on the use of the system, Quality information from SIKD had no positive effect on the use of system, The reciprocal relationship of satisfaction and use of system had no positive effect, Â Satisfaction of local government officer had positive influence on individual impact of each officer and the use of SIKD no positive effect on individual impact of each officer.